2013
DOI: 10.1371/journal.pone.0065465
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition in Male Rat Models under Different Nutritional Status and Physical Activity and Its Association with Serum Leptin and Ghrelin Levels

Abstract: BackgroundSeveral evidences indicate that gut microbiota is involved in the control of host energy metabolism.ObjectiveTo evaluate the differences in the composition of gut microbiota in rat models under different nutritional status and physical activity and to identify their associations with serum leptin and ghrelin levels.MethodsIn a case control study, forty male rats were randomly assigned to one of these four experimental groups: ABA group with food restriction and free access to exercise; control ABA gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
309
4
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(346 citation statements)
references
References 49 publications
17
309
4
16
Order By: Relevance
“…Recent studies found that gut microbiota dynamics are also regulated by metabolism changes, such as through physical exercise or diet change [25][26][27][28]. Interestingly, physical exercise modulates different population of gut bacteria in compared to food restriction or rich diet [29], and alleviates gut syndromes to toxin intake [30]. It is also noted that regardless of genetic background, exercise could induce gut microbiota composition changes in different lines of animals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that gut microbiota dynamics are also regulated by metabolism changes, such as through physical exercise or diet change [25][26][27][28]. Interestingly, physical exercise modulates different population of gut bacteria in compared to food restriction or rich diet [29], and alleviates gut syndromes to toxin intake [30]. It is also noted that regardless of genetic background, exercise could induce gut microbiota composition changes in different lines of animals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Given that nutritional status, dietary factors, physical activity and age have an important influence on the composition of the gut microbial community [54,55] it is not surprising that appetite-regulating hormones other than PYY, GLP-1 and GLP-2 will also interact with the gut microbiota in shaping appetite and metabolic status. Emerging evidence indicates that this applies to ghrelin [55,56], cholecystokinin [56] as well as leptin [56].…”
Section: Interaction Of the Gut Microbiota With Gut Peptidesmentioning
confidence: 99%
“…Emerging evidence indicates that this applies to ghrelin [55,56], cholecystokinin [56] as well as leptin [56]. In addition, germfree mice have a smaller number of enteroendocrine cells than conventionally colonized animals [56].…”
Section: Interaction Of the Gut Microbiota With Gut Peptidesmentioning
confidence: 99%
“…Evans, et al [25] proposed that physical exercise Short term (6 days) voluntary exercise showed that nutritional status and physical activity alter gut microbiota diversity in different manners. When exercise is combinated with food restriction protocol (restricting access for 23 hours per day and confined to running wheels except during a 60 min meal), a negative impact on bacterial richness is reported with respect to the Lactobacillus and Bifidobacterium genera [30]. The caloric restriction was also able to modify the phyla, even in the presence of exercise [30] (Table 1).…”
Section: The Effect Of Physical Exercise On the Gut Microbiotamentioning
confidence: 99%
“…When exercise is combinated with food restriction protocol (restricting access for 23 hours per day and confined to running wheels except during a 60 min meal), a negative impact on bacterial richness is reported with respect to the Lactobacillus and Bifidobacterium genera [30]. The caloric restriction was also able to modify the phyla, even in the presence of exercise [30] (Table 1). It seems that exmodifies the bacterial balance in the gut, with alteration of the major phyla levels, and increase of the relative proportion of butyrate-producing bacteria (Clostridiaceae, Lachnospiraceae and Ruminococcaceae).…”
Section: The Effect Of Physical Exercise On the Gut Microbiotamentioning
confidence: 99%